2012
DOI: 10.1007/s10067-011-1918-8
|View full text |Cite
|
Sign up to set email alerts
|

The practical value of biologics registries in Africa and Middle East: challenges and opportunities

Abstract: Biologics, including tumor necrosis factor (TNF) inhibitors, are increasingly used for the treatment of inflammatory conditions such as rheumatoid arthritis (RA), psoriatic arthritis, and ankylosing spondylitis. The efficacy of these drugs has been demonstrated in randomized controlled trials (RCTs). However, these studies are conducted in controlled environments, and the results may not necessarily reflect clinical outcomes in daily clinical practice. In Europe and other western countries, numerous biologics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In the future, a national registry should be established to help in documenting and improving outcomes of treatment for immune-mediated diseases. 45 …”
Section: Discussionmentioning
confidence: 99%
“…In the future, a national registry should be established to help in documenting and improving outcomes of treatment for immune-mediated diseases. 45 …”
Section: Discussionmentioning
confidence: 99%
“…4 However, there are few large epidemiological studies or good-quality registry data to suggest the disease's overall prevalence in the region of the Arabian Gulf. [5][6][7] Small population and hospital-based studies give wide variation, from 0.19% in rural Iran to 1.0% of the adult population in Lebanon and Iraq. [8][9][10][11][12] In Oman, the prevalence of RA in the population has been calculated at 8.4 cases per 1,000 adults (0.84%).…”
Section: Ra Management In the Arabian Gulfmentioning
confidence: 99%
“…The increased interest perhaps results from the numerous papers highlighting the suboptimal management of RA in this region and the consequent calls to collect further epidemiological data from across the region to increase understanding of the intra-and intercountry variability of the disease, set up registries to monitor the safety of newer treatments and raise awareness of the impact and burden of this condition among physicians and patients, develop national recommendations for managing RA and monitoring comorbidities, and improve training of HCPs from all relevant disciplines so that they can recognise early inflammatory arthritis and make appropriate referral and fast-track patients to ensure earlier introduction of intensive treatment, thus minimising disease activity as soon as possible after diagnosis [1,[13][14][15][16][17]. Encouragingly, Zafar et al found that the introduction of support groups, awareness programmes and public campaigns in the UAE in recent years had significantly reduced the time to diagnosis and initiation of DMARD therapy, although they recommended larger studies to substantiate this further and to address whether shorter times to diagnosis and to treatment can positively influence rates of remission and quality of life [18].…”
Section: Discussionmentioning
confidence: 99%